2007
DOI: 10.4049/jimmunol.179.4.2532
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Immune Response to Mycobacterium tuberculosis Infection in the Guinea Pig

Abstract: Pulmonary tuberculosis in guinea pigs is an extremely useful model for drug and vaccine testing due to the fact that its pathological disease process is similar to that present in humans. Progress in this field has been hindered because the tools necessary to undertake a complete immunological analysis of the guinea pig cellular immune response against Mycobacterium tuberculosis have been lacking. In this study, we combined a new flow cytometric gating strategy with immunohistochemistry to track T cells, B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 42 publications
6
110
0
Order By: Relevance
“…Since lactoferrin is a component of secretory granules of both macrophages and granulocytes, it is released into the extra-cellular space following inflammatory cell degranulation at sites of inflammation (55). We have recently shown by flow cytometry and immunohistochemistry that granulocyte necrosis and degranulation are associated with the development of primary lesion necrosis, a pattern that matches that of extra-cellular lactoferrin in the current study (56). By being more resistant to oxidative modification, lactoferrin may maintain its iron binding and sequestering capacity at sites of inflammation, when released with reactive oxygen species and myeloperoxidase from stimulated and degranulating neutrophils (57).…”
Section: Discussionsupporting
confidence: 75%
“…Since lactoferrin is a component of secretory granules of both macrophages and granulocytes, it is released into the extra-cellular space following inflammatory cell degranulation at sites of inflammation (55). We have recently shown by flow cytometry and immunohistochemistry that granulocyte necrosis and degranulation are associated with the development of primary lesion necrosis, a pattern that matches that of extra-cellular lactoferrin in the current study (56). By being more resistant to oxidative modification, lactoferrin may maintain its iron binding and sequestering capacity at sites of inflammation, when released with reactive oxygen species and myeloperoxidase from stimulated and degranulating neutrophils (57).…”
Section: Discussionsupporting
confidence: 75%
“…189 TB is also a primarily hematogenously disseminated disease in the guinea pig. 189 Pulmonary lesions in the guinea pig also contain a high proportion of granulocytes, particularly eosinophils, 152 which are not common features of the human disease. Furthermore, although inbred strains of guinea pigs are available, they are not well characterized with respect to Mtb infection, and immune responsiveness and reagents, although improving, are limited.…”
Section: Guinea Pigsmentioning
confidence: 99%
“…We observed that the number of peripheral IFN-␥ SFCs as well as the circulating levels of IFN-␥ in serum was reduced at 1 month postinfection. The recruitment of IFN-␥-positive T cells to the site of infection might be responsible for the apparent reduction of T cell response which we observed in the blood (27,29). However, regulatory T cells which develop during active disease may also prevent the specific IFN-␥ SFC response to RD-1 antigens (7,21).…”
Section: Discussionmentioning
confidence: 42%